FATE: Feminisation, Agricultural Transition and rural Employment - Birachi, Eliud Abucheli; Zamora, Elizabeth Jimenez; Phommavong, Saithong; Upreti, Bishnu Raj; Schnegg, Brigitte; Bieri, Sabin; Cook, Sarah; Seguino, Stephanie; Tsikata, Dzodzi; Wobst, Peter (2013)
Project summary and description of the FATE project (Feminisation, agricultural transition and rural employment) - social and political conditions of asset building in the context of export-led agriculture